A multinational, multicentre study on the psychological outcomes and associated physical symptoms amongst healthcare workers during COVID-19 outbreak - Chew, Nicholas WS (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
10.1016/j.bbi.2020.04.049